Type 2 diabetes and/or its treatment leads to less cognitive impairment in Alzheimer's disease patients - Dominguez, Raul Omar (2012)
Aim: To evaluate the cognitive performance of a homogeneous population of Alzheimer's disease (AD), non-demented Type 2 Diabetes Mellitus (DIAB), demented with concomitant diseases (AD+DIAB) and healthy control subjects. AD is a progressive dementia disorder characterized clinically by impairment of memory, cognition and behavior. Recently, a major research interest in AD has been placed on early evaluation. Diabetes is one of the clinical conditions that represent the greatest risk of developing oxidative stress and dementia. Glucose overload, leading to the development of impaired-induced insulin secretion in DIAB and has been suggested to slow or deter AD pathogenesis. Methods: The degree of cognitive impairment was determined on the Alzheimer Disease Assessment Scale-Cognitive (ADAS-Cog) and the Folstein's Mini Mental State Examination (MMSE); the severity of dementia was quantified applying the Clinical Dementia Rating (CDR) test; the Hamilton test was employed to evaluate depressive conditions; the final population studied was 101 subjects. Results: The cognitive deterioration is statistically significantly lower (p<0.05) in AD+DIAB patients as compared with AD patients. Conclusions: In this longitudinal study the superimposed diabetic condition was associated with a lower rate of cognitive decline, while diabetic non-demented patients and controls present normal scores. © 2012 Elsevier Ireland Ltd.